THE MODERATING IMPACT OF INCOME SMOOTHING ON THE INCREMENTAL INFORMATION CONTENT OF CASH FLOWS - Sutopo, Bambang (Magister Manajemen, Fakultas Ekonomika dan Bisnis Undip, 2003)
The objective of this study is to investigate the moderating impact of income smoothing on the incremental information content of cash flow. More specifically, this study examines whether cash flows have incremental information content beyond earnings for the higher income-smoothing index. The cash flows information include both information of total cash flows (hypothesis 1) and information of cash flows from operating, investing, and financing activities (hypothesis 2). The hypotheses are tested applying contextual models, i.e., cumulative abnormal returns (CAR) are regressed on unexpected earnings, unexpected cash flows, the interaction between unexpected earnings and income smoothing index, and the interaction between unexpected cash flows and income smoothing index.Using observation period 1995-1996 with 91 cases, results of this study show that the null hypothesis 1 and the null hypothesis 2 can be rejected, primarily for event window [O, +5]. The results of this study indicate the moderating impact of income smoothing on incremental information content of cash flows. For the higher income-smoothing index, cash flows have incremental information content beyond earnings. Therefore, the cash flows information as stated in the PSAK No. 2 is useful to investor, specifically for the higher income smoothing index.